Смуглая ведьма: [роман] / Нора Робертс ; [перевод с английского С. Володина] - Робертс Нора (Нора Робертс, 2015)
Экземпляры: (20151127) / Инвентарный номер: 49135 / Цена: 244.97 / Сис.шифр: 84(3) / Авт.знак: Р 58 / ББК: 84(7Сое)